2019
DOI: 10.3390/ijms20246301
|View full text |Cite
|
Sign up to set email alerts
|

4-methylumbelliferone Prevents Liver Fibrosis by Affecting Hyaluronan Deposition, FSTL1 Expression and Cell Localization

Abstract: 4-methylumbelliferone (4MU) is an inhibitor of hyaluronan deposition and an active substance of hymecromone, a choleretic and antispasmodic drug. 4MU reported to be anti-fibrotic in mouse models; however, precise mechanism of action still requires further investigation. Here we describe the cellular and molecular mechanisms of 4MU action on CCl4-induced liver fibrosis in mice using NGS transcriptome, Q-PCR and immunohistochemical analysis. Collagen and hyaluronan deposition were prevented by 4MU. The CCl4 stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Furthermore, we demonstrated that there was a TGF-β1-miR29a-Fstl1 regulatory circuit mediating liver fibrosis. These results are in agreement with previous studies showing Fstl1 was induced in liver fibrosis by CCl 4 treatment [40]. Our observation also confirmed the previous studies that knockdown Fstl1 attenuate liver fibrosis [25,26].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, we demonstrated that there was a TGF-β1-miR29a-Fstl1 regulatory circuit mediating liver fibrosis. These results are in agreement with previous studies showing Fstl1 was induced in liver fibrosis by CCl 4 treatment [40]. Our observation also confirmed the previous studies that knockdown Fstl1 attenuate liver fibrosis [25,26].…”
Section: Discussionsupporting
confidence: 94%
“…Throughout, data represent means ± SEM. *P < 0.05, **P < 0.01, ***P < 0.001 altered macrophage localization with the downregulation of Fstl1 in CCl 4 treated mice [40]. Further studies are needed to determine whether Fstl1 modulates inflammatory responses in liver fibrosis.…”
Section: Discussionmentioning
confidence: 96%
“…HA bioactivity is dependent on its molecular weight, enzymatic synthesis, and endogenous versus exogenous application [55,201,202]. The disruption or prevention of HA pericellular coat synthesis using hyaluronidase enzymes [203], HAS inhibitors [204,205] or exogenous HA oligosaccharides [59] results in the failure of TGF-β1-stimulated myofibroblast phenotypic acquisition. The inhibition of HAS2 activity [206] or global HAS synthesis of HA [204,205] have demonstrated preventative effects in various models of fibrosis.…”
Section: Experimental and Pre-clinical Interventions For Myofibroblast Differentiationmentioning
confidence: 99%
“…The disruption or prevention of HA pericellular coat synthesis using hyaluronidase enzymes [203], HAS inhibitors [204,205] or exogenous HA oligosaccharides [59] results in the failure of TGF-β1-stimulated myofibroblast phenotypic acquisition. The inhibition of HAS2 activity [206] or global HAS synthesis of HA [204,205] have demonstrated preventative effects in various models of fibrosis. However, given the ubiquitous role of HAS-synthesised HA in tissues, and the lack of specific HAS isoenzyme inhibitors, it is unclear at present whether the inhibition of HA synthesis would be beneficial in a clinical setting.…”
Section: Experimental and Pre-clinical Interventions For Myofibroblast Differentiationmentioning
confidence: 99%
“…Recent experimental data reveal hyaluronan synthase 2 (HAS2) as an important drug target in fibrosis ( Andreichenko et al. 2019 ; Yang et al.…”
Section: Introductionmentioning
confidence: 99%